2007
DOI: 10.1037/0278-7393.33.1.238
|View full text |Cite
|
Sign up to set email alerts
|

The role of memory for past test in the underconfidence with practice effect.

Abstract: According to the Memory for Past Test (MPT) heuristic, judgments of learning (JOLs) may be based, in part, on memory for the correctness of answers on a previous test. The authors explored MPT as the source of the underconfidence with practice effect (UWP; A. Koriat, L. Sheffer, & H. Ma'ayan, 2002), whereby Trial 1 overconfidence switches to underconfidence by Trial 2. Immediate and delayed JOLs were contrasted because only immediate JOLs demonstrate UWP. Consistent with MPT for immediate JOLs, Trial 1 test pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
163
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(184 citation statements)
references
References 32 publications
(41 reference statements)
18
163
3
Order By: Relevance
“…Finn and Metcalfe (2007;2008) have suggested that participants may rely on Memory for Past Test (MPT) when predicting future memory performance if they had already been tested on the same material. That is, when judging the future memorability of information, people base their judgments on whether that information was recalled during a previous test.…”
Section: Metamemorymentioning
confidence: 99%
See 4 more Smart Citations
“…Finn and Metcalfe (2007;2008) have suggested that participants may rely on Memory for Past Test (MPT) when predicting future memory performance if they had already been tested on the same material. That is, when judging the future memorability of information, people base their judgments on whether that information was recalled during a previous test.…”
Section: Metamemorymentioning
confidence: 99%
“…The reliance on MPT suggests that participants generally do not take new learning into account when predicting future memory performance, leading to a stability bias in memory (Finn & Metcalfe, 2007;2008;Kornell & Bjork, 2009). That is, although participants may understand that more study opportunities will be helpful for memory, the MPT cue may overshadow these beliefs and guide item-by-item predictions.…”
Section: Metamemorymentioning
confidence: 99%
See 3 more Smart Citations